Role of immunotherapy in Ewing sarcoma. Issue 2 (8th December 2020) - Morales, Erin; Olson, Michael; Iglesias, Fiorella; Dahiya, Saurabh; Luetkens, Tim; Atanackovic, Djordje
Abstract : Ewing sarcoma (ES) is thought to arise from mesenchymal stem cells and is the second most common bone sarcoma in pediatric patients and young adults. Given the dismal overall outcomes and very intensive therapies used, there is an urgent need to explore and develop alternative treatment modalities including immunotherapies. In this article, we provide an overview of ES biology, features of ES tumor microenvironment (TME) and review various tumor-associated antigens that can be targeted with immune-based approaches including cancer vaccines, monoclonal antibodies, T cell receptor-transduced T cells, and chimeric antigen receptor T cells. We highlight key reasons for the limited efficacy of various immunotherapeutic approaches for the treatment of ES to date. These factors include absence of human leukocyte antigen class I molecules from the tumor tissue, lack of an ideal surface antigen, and immunosuppressive TME due to the presence of myeloid-derived suppressor cells, F2 fibrocytes, and M2-like macrophages. Lastly, we offer insights into strategies for novel therapeutics development in ES. These strategies include the development of gene-modified T cell receptor T cells against cancer–testis antigen such as XAGE-1, surface target discovery through detailed profiling of ES surface proteome, and combinatorial approaches. In summary, we provide state-of-the-art science in ES tumor immunology and immunotherapy, with rationale and recommendations for future therapeutics development.